Bilingualisme dalam Masyarakat Kelurahan Lipatkain Kecamatan Kampar Kiri Kabupaten Kampar - Sundari, Meylani; Erni, Erni (UIR PRESS, 2021)
Indonesian society in general is a bilingual society and even multilingualism this is due to a multiethnic society with various ethnic groups. He said multiligualism because the Indonesian people master and use many or more than two languages. People in the Village of Lipatkain, Kampar Kiri District, Kampar Regency generally use bilingualism in their daily lives. The community uses the regional language and Indonesian language. This study examines two problems, namely (1) what are the types of bilingualism in the community of Lipatkain Village, Kampar Kiri District, Kampar Regency?, and (2) What are the types of bilingualism found in the community of Lipatkain Village, Kampar Kiri District, Kampar Regency?. The research approach that the author uses is a qualitative approach. The research method that the author uses is descriptive method. Based on the results of this study, there are (1) types of bilingualism found in the Village of Lipatkain, Kampar Kiri District, Kampar Regency, namely the types of bilingualism in regional languages ​​and Indonesian while the types of Indonesian and foreign languages ​​bilingualism are not found and, (2) the types of bilingualism found in the Village of Lipatkain. Kampar Kiri District, Kampar Regency, which is the type of multiple bilingualism, while the equivalent type of bilingualism is not found